2000
DOI: 10.1007/s002470000264
|View full text |Cite
|
Sign up to set email alerts
|

Cephaloskeletal dysplasia (Taybi-Linder syndrome; osteodysplastic primordial dwarfism type III): report of two cases and review of the literature

Abstract: We report two unrelated infants with cephaloskeletal dysplasia or Taybi-Linder syndrome, also referred to as osteodysplastic primordial dwarfism Type III. They presented with peculiar facial features, microcephaly and skeletal and cerebral abnormalities documented radiographically and with cranial MRI and/or CT. Some dissimilarities were observed in the skeletal findings between the two patients, most likely reflecting phenotypic variability within the same disorder. Some radiographic features were shown to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Earlier on we have described two male sibs with MOPD I with pigmentation abnormalities: lack of retinal pigmentation, fair hair color, and cutaneous albinism [Abdel‐Salam et al, ]. This has not been reported previously (Table ) [Winter et al, ; Haan et al, ; Meinecke and Passarge, ; Meinecke et al, ; Sigaudy et al, ; Vichi et al, ; Klinge et al, ; Juric‐Sekhar et al, ; Nagy et al, ]. Subsequently, Pierce and Morse [] described two sibs with MOPD I who lacked retinal pigment as well.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Earlier on we have described two male sibs with MOPD I with pigmentation abnormalities: lack of retinal pigmentation, fair hair color, and cutaneous albinism [Abdel‐Salam et al, ]. This has not been reported previously (Table ) [Winter et al, ; Haan et al, ; Meinecke and Passarge, ; Meinecke et al, ; Sigaudy et al, ; Vichi et al, ; Klinge et al, ; Juric‐Sekhar et al, ; Nagy et al, ]. Subsequently, Pierce and Morse [] described two sibs with MOPD I who lacked retinal pigment as well.…”
Section: Discussionmentioning
confidence: 66%
“…In their original description of MOPD I, Taybi and Linder [] described a male patient with an absent callosal body and large interhemispheric cyst, a combined lateral and third ventricle, and microscopic evidence of neuronal migration defects. Vichi et al [] subsequently reported two unrelated boys of whom one had similar brain findings. Subsequently, two other MOPD I patients showed these brain findings as well [Juric‐Sekhar et al, ; Abolila et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…MOPD I was first described by Taybi and Linder [1967] as cephaloskeletal dysplasia and fewer than 30 cases have been reported [Thomas and Nevin, 1976; Winter et al, 1985; Haan et al, 1989; Meinecke and Passarge, 1991; Meinecke et al, 1991; Eason et al, 1995; Berger et al, 1998; Sigaudy et al, 1998; Vichi et al, 2000; Klinge et al, 2002; Juric‐Sekhar et al, 2011]. Skeletal findings in MOPD I include platyspondyly and vertebral clefting, horizontal acetabular roofs, elongated and curved clavicles, and short long bones with enlarged metaphyses including age‐dependent bowing and undermodeled long bones.…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently suggested that types I and III were part of the same clinical spectrum with subtle variations among brain anomalies and radiographic changes (4); the two types have generally been combined since that time. Only 31 individuals with MOPD I/III from 25 families worldwide were reported in the literature through to 2010 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%